The middle -income class in the Philippines identifying the middle households using statistical models. - Clamor, Rachel C. (University of the Philippines, 2016)
Abstract (The middle-income class is claimed to be the key to economic greatness and stability. Bridsall et. al. (2000) defined it as the large group of households that are neither wealthy nor poor, that form the backbone of both the market economy and of democracy in most advanced societies. In this regard, it as deem necessary to identify the middle-income families and study their characteristics, so that the government could give them the needed support from the policies that it makes, particulary on taxation. However, as of this writing, there is still no standard definition or income threshold for the middle income class. This study builds on the existing middle-income classification models by Virola et al. (2007, 2010, 2013) and Albert et al. (2015). The proposed model excludes the poor and near-poor families in clustering analysis to establish three middle-income class intervals. Characteristics of the middle-income class are determined using an Ordered Logit Model with demographic and socio-economic characteristics as regressors for the income classifications. Results show an annual per capita income bracket of about PhP 80 thousand to at most PhP 185 thousand for the 'Lower Middle Class'. PhP 185 thousand to at most Php 185 thousand for 'Broad Middle Class', and PhP 405 thousand to at most PhP 1 million for the 'Upper Middle Class'. The projected number of middle-income families in 2016 is around 3.7 million. The results of this study will be vital in the updating of taxation policies of the century).